Elevated hepcidin serum level in response to inflammatory and iron signals in exercising athletes is independent of moderate supplementation with vitamin C and E - Díaz, Víctor; Peinado, Ana B.; Barba‐Moreno, Laura; Altamura, Sandro; Butragueño, Javier; González‐Gross, Marcela; Alteheld, Birgit; Stehle, Peter; Zapico, Augusto G.; Muckenthaler, Martina; Gassmann, Max (Physiological reports, 2015)
Iron deficiency among endurance athletes is of major concern for coaches, physicians, and nutritionists. Recently, it has been observed that hepcidin, the master regulator of iron metabolism, was upregulated after exercise and was found to be related to interleukin-6 (IL-6) elevation. In this study performed on noniron deficient and well-trained runners, we observed that hepcidin concentrations remain elevated in response to inflammatory and iron signals despite a 28-days supplementation period with vitamins C (500 mg/day) and E (400 IU/day).
Gesehen am 25.05.2020